High-resilience cotton base yarn for anti-wrinkle and durable heat-insulation fabric. (1st May 2021) - Wang, Kai; Fu, Chiyu; Wang, Rui; Tao, Guangming; Xia, Zhigang
Abstract: The hollow structural yarn of cellulose fibers can be easily flattened to remove their heat insulation ability and folded to incur unfavorable wrinkles. In contrast, natural hollow bamboos are flexible and shape-preserving with regard to external forces, and hollow cocoons are heat insulating to protect silkworms. Inspired by hollow bamboos and cocoons, a high resilience cotton base (i.e., silicon tube/cotton composite hollow, denoted as SCH) yarn was constructed by embedding a continuous hollow silicon tube into the cotton wrapping sheath, aiming to mitigate hollow cellulose yarn collapse and wrinkle problems. Comparatively, three other structural cotton base yarns were also designed: cotton core (CC), vinylon-core/cotton-sheath (VC) and vinylon-dissolved cotton hollow (VCH) yarns. ABAQUS CAE was applied to conduct a comparative theoretical finite element analysis of the heat transfer performance of the four different yarns. The theoretical analysis results indicated that the SCH yarn showed the minimum heat transfer performance to obtain maximum heat insulation. Then, the CC, SCH, VC and VCH yarns were fabricated into woven fabrics. The corresponding yarn structure, properties and fabric performance were comparatively analyzed. The analyzed results indicated that the SCH yarn was stronger and more elastic than other yarns, resulting in a maximum anti-wrinkle performance. The compression rebound ratio of the SCH yarn fabric (85.07%) was much higher than that of the VCH yarn fabric (18.78%) and other fabrics, indicating the excellent recovery ability of the SCH yarn. Different from other yarns, SCH yarn stored static air in the silicone tube, allowing a minimum permeability of air. Accordingly, the SCH yarn fabric had a more durable heat insulation rate than the other yarn fabrics.